APLIKASI MODEL E-MARKETPLACE DALAM E-AGRIBUSINESS - Hilmi Arija Fachriyan; I Putu Eka Wijaya (Universitas Wahid Hasyim, 2018)
Economic activity is currently entering an era called the era of digital economy. Digital economy involves the process of e-business or e-commerce that utilizes the internet network. The rapid growth of internet users in Indonesia has affected the agribusiness sector to adopt e-commerce called e-agribusiness.In line with the development of the internet, a new understanding of electronic marketing paradigm in e-agribusiness in the form of e-marketplace. Some agribusiness e-marketplace sites have been born in Indonesia such as